EDUKASI MANAJEMEN BISNIS UNTUK MEMBANGUN KEMANDIRIAN FINANCIAL PANTI ASUHAN - Annisa Fatimah (Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of this activity to provide knowledge sharing related to business management to build financial independence of the orphanage through business management training at the Al - Husna Orphanage - Malang. The first step for this program is to open the mind of the orphanage children that they must be financially independent after leaving the orphanage. In addition, the marketing potential for entrepreneurs is widely open for them. Fostering entrepreneurial ideas, planning strategies to marketing continue to evolve into today's society's needs. It is objected that the presence of lecturers and students who are also entrepreneurial practitioners will provide insight and meaningful new knowledge for all participants.